To mow or not to mow? Plant functional traits help to understand management impact on rich fen vegetation. Issue 1 (19th January 2019) - Kozub, Łukasz; Goldstein, Klara; Dembicz, Iwona; Wilk, Mateusz; Wyszomirski, Tomasz; Kotowski, Wiktor
Abstract: Questions: Fens are important conservation targets in temperate Europe. When hydrologically undisturbed, fens remain open for millennia. However, unaltered fens are scarce, and today their biodiversity largely depends on conservational mowing applied to prevent successional shifts. However, the effects on community structure and conservation values are uncertain, and management might not always be needed where it is a priori applied by managers. Thus, within the presented study, we ask the following questions: (a) How is the species and functional composition of fens influenced by mowing? (b) Does mowing increase the conservation value of fen ecosystems? Location: Lowland fens, northern Poland. Methods: The sample consisted of 27 pairs of mown and unmown plots, located within ten sites. Ordination methods were used to assess the influence of mowing on species composition. Functional traits related to competitiveness, flowering time, mycorrhizal associations and functional groups were used to characterize plant communities and species richness, and the number of specialist and red‐listed species was used to evaluate conservation values. Differences between mown and unmown plots were assessed using linear mixed‐effect models and the effect size approach. Results: Management of fens suppresses the growth of trees, shrubs and highly competitive herbaceous species and inhibits the encroachment of Sphagnum mosses. At the same time, it enhances the establishment of species from other ecosystems (grasses, ruderal species, species of drier sites) within fens and alters the microtopography of the fen surface. Conclusions: Mowing can enhance species richness and the presence of rich fen specialists in transformed sites, but it can lead to fen ecosystem deterioration towards managed meadow communities within sites sustaining many typical fen species and functional characteristics. Abstract : Fens are important conservation targets. However, the effects of often applied conservational mowing on their characteristics are uncertain. We studied fens in northern Poland to assess the influence of mowing on their species and functional composition as well as their conservation value. We conclude that mowing can lead to ecosystem deterioration within sites sustaining many fen species and proper functional characteristics.